Эвристический научный текст как объект стилистики (на материале русского и английского языков) - Стеванович, Раиса; Stevanovich, Raisa (Східноєвропейський національний університет імені Лесі Українки, 2015)
В данной статье представлен сравнительный анализ стилистических особенностей русских и английских научных текстов, рассматривается архитектоника их построения, где ведущую роль играет автор научного текста, особенности его восприятия мира, что находит отражение в эвристических текстах, связанных с мыслительной деятельностью, подчеркиваются различия в картине мира англичан и русских. В статье исследуются также лексические и грамматические особенности научных текстов в их сравнении, анализируются различные парадигмы, выделенные в научных текстах. The given article deals with a comparative analysis of stylistic peculiarities of English and Russian scientific texts, where the author of these texts plays the most important part, as he creates the texts and his or her vision of the surrounding world is clearly reflected in these texts. The scientific texts are analysed herewith from lexical and grammatical points of view, different linguistic paradigms are analysed showing that scientific thinking is closely connected with a common sense which is illustrated by the scientific texts. It is emphased that it is obligatory to study scientific texts together with the author of the texts where his individual features of a living being are clearly seen and reflected in the texts. It is shown that scientific text demonstrates the intelligence of the author who at the same time is its addressee.
Representation of a heuristic scientific text as an object of stylistics(based on English and Russian scientific texts)
Keywords: эвристический научный текст; парадигма; сравнительный анализ; картина мира; scientific heuristic text; paradigm; comparative analysis; author; common sense